A Study on Music Consumption Behavior and Marketing Strategies on the TikTok Platform - Chengxuan Wang; Yaqi Zhang; Yifan Zhang; Xiaoyu Fan (International Journal of Economics, Commerce, and Management, 2026)
The development of digital technology has significantly transformed music consumption and marketing strategies in the creative industry. The shift from physical media to digital platforms, especially short-form video-based social media like TikTok, has created a new ecosystem that emphasizes interactivity, community participation, and organic music distribution. TikTok allows users to incorporate song snippets into creative content, positioning music as both entertainment and a symbol of digital identity. This shift reveals that music popularity is now primarily driven by recommendation algorithms and user-generated content rather than traditional promotion. This study adopts a qualitative descriptive approach with phenomenological analysis to explore the relationship between music consumption behavior and marketing strategies on TikTok. Findings indicate that algorithms act as digital curators, influencing audience preferences, while user participation accelerates the viral spread of songs through challenges, remixes, and content reproduction. Effective music marketing strategies must be data-driven, trend-responsive, and capable of leveraging users' emotional and social engagement. TikTok thus serves not only as a distribution platform but also as a space for constructing global popular culture. This study contributes to digital media scholarship and offers practical implications for designing sustainable marketing strategies in the ever-evolving digital ecosystem.